Pelaksanaan Pendidikan Islam Saat Pembelajaran Tatap Muka (PTM) Terbatas di MIN 1 Lubuklinggau - Susanti, Susi; Warlizasusi, Jumira; Sumarto (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2023)
The COVID-19 pandemic has changed the pattern of education significantly. Learning that has been normal and carried out face-to-face has been transferred to online learning in order to suppress the spread of the COVID-19 virus. As the COVID-19 case in Lubuklinggau City has slowed, the local government has issued a policy to enforce Limited Face-to-Face Learning (PTM) in education units. For educational units that are ready to implement Limited PTM, there are several components of a health protocol that must be prepared. This study uses a descriptive method with a qualitative approach. The results of the study revealed that the implementation of Islamic education during Limited Face-to-Face Learning (PTM) at MIN 1 Lubuklinggau has been going well. Of course, Islamic education programs such as Friday Barokah/reading Surah Yaasin together and the Al-Qur'an Reading and Writing Program everyday will continue to be carried out, of course, while still implementing disciplined health protocols